2009
DOI: 10.1128/jcm.02464-08
|View full text |Cite
|
Sign up to set email alerts
|

High Concentrations of Manganese in Mueller-Hinton Agar Increase MICs of Tigecycline Determined by Etest

Abstract: MICs of tigecycline determined by Etest were 4 to 12 times (three ATCC strains) and 2 to 8 times (50 clinical isolates) higher in Mueller-Hinton agar from Merck than in Mueller-Hinton agar from either Oxoid or Difco. This was related to a much higher concentration of manganese in the medium from Merck.Tigecycline is the first glycylcycline approved for clinical use (16). It can be oxidized when added to a broth medium that has been oxygenated during storage (13) or when tigecycline-containing broth is stored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…This resulted from high minor error rates (19.6 to 37.4% for minocycline and 23.4 to 63.6% for tigecycline), most of which represented a shift from the susceptible category to the intermediate category (or the corresponding categories for tigecycline). This phenomenon has been well documented for tigecycline (23,24) and more recently for minocycline as well (8). Many of these minor errors could be attributed to incremental MIC differences afforded by the granularity of Etest readings, i.e., a shift from 4 g/ml (reference) to 6 g/ml (Etest) for minocycline and from 2 g/ml (reference) to 3 g/ml (Etest) for tigecycline.…”
Section: Discussionmentioning
confidence: 83%
“…This resulted from high minor error rates (19.6 to 37.4% for minocycline and 23.4 to 63.6% for tigecycline), most of which represented a shift from the susceptible category to the intermediate category (or the corresponding categories for tigecycline). This phenomenon has been well documented for tigecycline (23,24) and more recently for minocycline as well (8). Many of these minor errors could be attributed to incremental MIC differences afforded by the granularity of Etest readings, i.e., a shift from 4 g/ml (reference) to 6 g/ml (Etest) for minocycline and from 2 g/ml (reference) to 3 g/ml (Etest) for tigecycline.…”
Section: Discussionmentioning
confidence: 83%
“…Due to poor reproducibility of its mineral content, the Mueller-Hinton medium may be unsuitable for this purpose. Whereas most commonly available test media probably have concentrations below the critical range, considerable variability in the concentration of divalent cations in Mueller-Hinton broth or agar from different manufacturers has been reported (11), and manganese concentrations in MuellerHinton agar that are well above 500 mg/liter have been found (5).…”
mentioning
confidence: 99%
“…Moreover, if the problem persists, even when using a new lot, the manufacturer should be contacted. Although there is no CLSI recommendation for manganese, iron, or zinc supplementation in the culture medium, diverse studies have shown that these ions can also influence the antimicrobial susceptibility tests results for other antimicrobial agents than polymyxin (13,16).…”
Section: Discussionmentioning
confidence: 99%
“…As the need for polymyxin usage increases in the clinical setting, routine microbiology laboratories must perform the polymyxin susceptibility testing under high-quality standard conditions. Since the cation composition of Mueller-Hinton agar (MHA) may vary among manufacturers and even among distinct lots of the same manufacturer (13), the aim of the present study was to determine the influence of different commercial brands of MHA for testing the polymyxin B susceptibility of A. baumannii and P. aeruginosa clinical isolates.…”
mentioning
confidence: 99%